2022
DOI: 10.30537/sjet.v5i1.958
|View full text |Cite
|
Sign up to set email alerts
|

MnO2@Co3O4 nanocomposite based electrocatalyst for effective oxygen evolution reaction

Abstract: For large-scale energy applications, conceiving low-cost and simple earth-abundant electrocatalysts are more difficult. By using an aqueous chemical technique, MnO2 was added into Co3O4 with varying concentrations to prepare MnO2@Co3O4 nanocomposite (CM). In an aqueous solution of 1 M KOH, the electrocatalyst with a greater concentration of MnO2 outperforms in terms of OER. To confirm the composition, crystalline structure, and morphology of the electrocatalyst, analytical methods such as X-ray diffraction (XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…However, there was only a significant difference observed between O-Co-O and Co-O metal oxide peaks at 667 cm -1 and 577 cm -1 , respectively [58,59]. FTIR studies indicated that higher concentrations of potassium chromate resulted in a decrease in metal oxide peaks, which indicates in situ growth of CrO0.87 and Co3O4.…”
Section: Crystal Quality Morphology and Surface Chemical Composition ...mentioning
confidence: 94%
“…However, there was only a significant difference observed between O-Co-O and Co-O metal oxide peaks at 667 cm -1 and 577 cm -1 , respectively [58,59]. FTIR studies indicated that higher concentrations of potassium chromate resulted in a decrease in metal oxide peaks, which indicates in situ growth of CrO0.87 and Co3O4.…”
Section: Crystal Quality Morphology and Surface Chemical Composition ...mentioning
confidence: 94%
“…In Figure 6c, the morphology of Ni-Fe-P-Se can be seen, which shows a higher amount of prepared material on NF, with varied surface features than both previous samples of Ni-P-Se and Fe-P-Se, respectively. Through the SEM images, we have observed agglomerated surface features of various elements within the as-prepared Ni-Fe-P-Se structure as a potential composite for electrochemical water splitting application [34,35].…”
Section:  / °mentioning
confidence: 96%
“…Numerous studies have been conducted to nd low-cost and earthabundant electrocatalysts that foster water oxidation. 17,18 Various transition-metal based oxides, 19,20 suldes, 21,22 phosphides, 23,24 selenides 25 electrocatalysts for water oxidation have been reported. Extensive studies have been performed for the development of efficient, facile, stable and earth abundant electrocatalysts for the hydrogen production due the fact that the complete exploitation of hydrogen fuel from water splitting is restricted by high energy demanding half-cell water oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%